Engine Exhaust Particulates - Agarwal, Avinash Kumar; Dhar, Atul.; Sharma, Nikhil; Shukla, Pravesh Chandra; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book provides a comparative analysis of both diesel and gasoline engine particulates, and also of the emissions resulting from the use of alternative fuels. Written by respected experts, it offers comprehensive insights into motor vehicle particulates, their formation, composition, location, measurement, characterisation and toxicology. It also addresses exhaust-gas treatment and legal, measurement-related and technological advancements concerning emissions. The book will serve as a valuable resource for academic researchers and professional automotive engineers alike. .
Characteristics of particulate matter at different combustion modes -- Emission of ultra-fine organic carbon particles in SI engine exhaust -- Fuel Stratification and Particulate Emissions from a Spark Ignition Direct Injection Engine -- Alternative Fuels For Particulate Control in Diesel Engines -- Effect on Particulate Emissions in a Diesel Engine due to Varying Boost and Exhaust Gas Recirculation (EGR) -- Particulate Emission from Gasoline Direct Injection Engines -- Effect on Human Health by Particulate Emissions -- Alternative Fuels for Particulate Reduction in a Gasoline Engine -- Composition and Formation of Diesel Engine Exhaust particulates -- Effect of Charge Preparation, Spray Characteristics and Cylinder Geometry on Particulate Emission in SI Engine -- Physicochemical properties of diesel exhaust particulates -- Alternative Fuels for Particulate Control in Diesel Engines -- Numerical modelling of soot in diesel engines -- A Comprehensive Review On Oxygenated Fuel Additive Options For Sustainable Emission Reduction From Diesel Engines -- Solid Particle Number Emission of Advanced Combustion Concepts (RCCI and PPC) on Compression Ignition Engines -- Particulate Reduction Using Exhaust Aftertreatment Devices in Diesel Engines -- Characteristics and Fundamentals of Particulates in Compression Ignition Engine -- Nano-Particle Emissions in Reactivity Controlled Compression Ignition Engine -- Particulate Emissions from Hydrogen Diesel fuelled CI Engines -- Effect of hydrogen and Producer gas addition on the Performance and Emissions on a Dual Fuel Diesel Engine -- Ultrafine Particles In Concern of Vehicular Exhaust -An overview -- DPF Active Regeneration system.
Keywords: Engines; Pollution; Transportation engineering; Traffic engineering; Cogeneration of electric power and heat; Fossil fuels; Engine Technology; Pollution; Transportation Technology and Traffic Engineering; Fossil Fuel